Persepsi Mahasiswa Terhadap Implementasi Model Deep Learning Dalam Pembelajaran Pkn Untuk Mengembangkan Kemampuan Berpikir Kritis Siswa SD - Amalia, Shofi Nur (Gayaku Publisher, 2025)
This study aims to explore the perceptions of students in the Primary School Teacher Education Program (PGSD) regarding the implementation of the deep learning model in Civic Education (PKn) learning to develop the critical thinking skills of elementary school students. The research method used was descriptive qualitative, involving 10 students as respondents representing the class. Data were collected through in-depth interviews focusing on two issues: (1) Factors influencing students' perceptions of the implementation of deep learning models in PKn learning, and (2) Students' descriptions of the effectiveness of deep learning models in improving elementary school students' critical thinking skills. The results showed that factors such as understanding of deep learning concepts, previous learning experiences, and learning facility support had a significant effect on students' perceptions. In addition, students described the deep learning model as an effective method in encouraging students to think critically, emphasizing interactivity and project-based learning. These findings provide new insights into the application of learning innovations at the elementary level and emphasize the need for further development in teacher training to maximize the potential of deep learning models in education.